Permissive Attitudes to Domestic Violence on Women in Indonesia - Oktriyanto; Arga Nugraha; Mardiana Dwi Puspitasari; Sri Lilestina Nasution; Ifa Prasetya Novianafari (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Violence against women occurs in almost all countries and has become a global issue that is often reviewed and discussed at various seminars. The United Nations defines violence against women as